Act or Wait-and-See? Adversity, Agility, and Entrepreneur Wellbeing across Countries during the COVID-19 Pandemic. (May 2023) - Stephan, Ute; Zbierowski, Przemysław; Pérez-Luño, Ana; Wach, Dominika; Wiklund, Johan; Alba Cabañas, Marisleidy; Barki, Edgard; Benzari, Alexandre; Bernhard-Oettel, Claudia; Boekhorst, Janet A.; Dash, Arobindu; Efendic, Adnan; et al.
How can entrepreneurs protect their wellbeing during a crisis? Does engaging agility (namely, opportunity agility and planning agility) in response to adversity help entrepreneurs safeguard their wellbeing? Activated by adversity, agility may function as a specific resilience mechanism enabling positive adaption to crisis. We studied 3162 entrepreneurs from 20 countries during the COVID-19 pandemic and found that more severe national lockdowns enhanced firm-level adversity for entrepreneurs and diminished their wellbeing. Moreover, entrepreneurs who combined opportunity agility with planning agility experienced higher wellbeing but planning agility alone lowered wellbeing. Entrepreneur agility offers a new agentic perspective to research on entrepreneur wellbeing.